Criminal Law Policy in Efforts to Overcome the Criminal Offence of Maltreatment Based on Restorative Justice by the Prosecutor's Office : (Research Study at the North District Attorney's Office) - T. Ikhsan Ansyari Husny; Rahmayanti Rahmayanti; Muhammad Arif Sahlepi (International Journal of Law and Society, 2024)
The crime of maltreatment is a deliberate act that causes injury, pain or even death to a person. However, efforts to resolve minor persecution crimes can be done through Restorative Justice. Restorative Justice can be done through mediation of victims of persecution. This research formulates the problem of knowing how the legal arrangements by the Prosecutor's Office on Restorative Justice and knowing how the efforts and obstacles to overcoming persecution crimes based on Restorative Justice by the North Padang Lawas State Attorney's Office. This research method is through empirical juridical research with field studies at the North Padang Lawas State Attorney's Office related to countermeasures against criminal acts of persecution based on Restorative Justice. The data collection technique used by the author in this research is Field Research, which includes data sourced from interviews with the Public Prosecutor at the North Padang Lawas State Attorney's Office. Data analysis used in this research is qualitative analysis. The process of applying Restorative Justice in the crime of persecution in the North Padang Lawas District Attorney's Office is carried out by means of the Public Prosecutor offering peace efforts to the victim and suspect. Based on cases that meet the criteria for Restorative Justice, the State Attorney's Office will write to the High Prosecutor's Office and the Deputy Attorney General's Office for General Crimes to seek approval for Restorative Justice. The North Padang Lawas District Attorney's Office prioritizes peace between victims and perpetrators in resolving cases of light maltreatment by involving the families of both parties, such as community leaders, without any pressure, coercion, or intimidation from the Public Prosecutor who acts as a facilitator.